2008
DOI: 10.1177/088840640803100205
|View full text |Cite
|
Sign up to set email alerts
|

Co-Teaching at the Pre-Service Level: Special Education Majors Collaborate with English Education Majors

Abstract: General education and special education teacher candidates lack experience in collaborating with each other as colleagues; however, upon graduating and entering their own classrooms, most are expected to know how to provide services to students with disabilities in the general classroom. This study describes the efforts of two professors, one in special education and the other in English education, to have their students participate in a collaborative and consultative relationship with each other at the pre-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Pugach and colleagues (2014) excluded survey and attitudinal studies from their analysis. Sixteen of the thirty studies included in the chapter included some form of assessments of preservice teachers (Andrews, 2002;Arndt & Liles, 2010;Brown, Welch, Hill, & Cipko, 2008;Frey, Andres, McKeeman, & Lane, 2012;Geer & Hammill, 2007;Golder, Norwich & Bayliss, 2005;Goodnough, Osmand, Dibbon, Glassman, & Stevens, 2009;Griffin, Jones, & Kilgore, 2006;Kamens, 2007;Kamens & Casale-Giannola, 2004;Kurtts, Hibbard, & Levin, 2005;Jeffs & Banister, 2006;Maheady, Jabot, Rey, & Michelli-Pendl, 2007;McHatton & Daniel, 2008;Sobel, Iceman-Sands, & Basile, 2007;Young, 2011a). One of the findings of the review revealed that when the term "diverse" appeared within the studies about collaboration, it was typically to reference the diversity of participants' academic or departmental backgrounds or to reference the diverse learning needs of P-12 learners.…”
Section: Assessments Of Collaborative Skillsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pugach and colleagues (2014) excluded survey and attitudinal studies from their analysis. Sixteen of the thirty studies included in the chapter included some form of assessments of preservice teachers (Andrews, 2002;Arndt & Liles, 2010;Brown, Welch, Hill, & Cipko, 2008;Frey, Andres, McKeeman, & Lane, 2012;Geer & Hammill, 2007;Golder, Norwich & Bayliss, 2005;Goodnough, Osmand, Dibbon, Glassman, & Stevens, 2009;Griffin, Jones, & Kilgore, 2006;Kamens, 2007;Kamens & Casale-Giannola, 2004;Kurtts, Hibbard, & Levin, 2005;Jeffs & Banister, 2006;Maheady, Jabot, Rey, & Michelli-Pendl, 2007;McHatton & Daniel, 2008;Sobel, Iceman-Sands, & Basile, 2007;Young, 2011a). One of the findings of the review revealed that when the term "diverse" appeared within the studies about collaboration, it was typically to reference the diversity of participants' academic or departmental backgrounds or to reference the diverse learning needs of P-12 learners.…”
Section: Assessments Of Collaborative Skillsmentioning
confidence: 99%
“…(2014) review (Bradley & Monda-Amaya, 2005;Griffin et al, 2006;McHatton & Daniel, 2008;McKenzie, 2009) were also included in the chapter.…”
Section: Handbook Of Research On Special Education Teacher Preparationmentioning
confidence: 99%
See 3 more Smart Citations